Sedimentary and drainage evolution of the Condamine Valley Transition Zone (eastern Australia). Issue 4 (19th May 2019) - Manchee, P.; Bianchi, V.; Shaanan, U.; Esterle, J.
Abstract: The basal succession of the Condamine Valley, which overlays the boundary between the Surat and Clarence-Moreton basins (eastern Australia), contains a clay-rich horizon 'the Transition Zone' that marks a pronounced unconformity between the Jurassic Walloon Coal Measures and the Quaternary Condamine Alluvium. This paper provides insights into the tectonic and drainage evolution of the Condamine Valley through integrated analysis of U–Pb ages of detrital zircon from three samples (494 concordant analyses), stable oxygen isotope analysis on eight authigenic clay samples, X-ray fluorescence of primary and trace elements, and hyperspectral mineral analysis from two drill cores (Lone Pine 17 and Daandine 164). The Transition Zone is interpreted to consist of both weathered Jurassic sediments and Cenozoic clay deposits. Two sequential cycles of erosion, deposition and pedogenesis, related to geomorphological and climatic conditions are recognised. Distinctive oxygen isotope signatures of the two weathering fronts demonstrated an initial Early Cretaceous phase (δ 18 O = 11.9–15.7‰ VSMOW) associated with laterisation and possible uplift, followed by Paleogene (δ 18 O = 16.4–17.3‰ VSMOW) silcretisation of reworked Jurassic sediments. Detrital zircon geochronology yielded Jurassic maximum constraints for the age of deposition of three samples that are indistinguishable within error, the oldest of which (163 ± 8 Ma from the lateritic profile) corresponds to the age of the underlying Walloon Coal Measures. The two overlaying samples from a silcrete profile and granular alluvium yielded overlapping yet younger ages of 150 ± 6 Ma and 156 ± 9 Ma, respectively. Vitrinite reflectance used as a proxy for the thermal condition of the coal strata enabled an estimated 2–3 km of burial and subsequent (likely Early Cretaceous) uplift. Geochemical insights from the Condamine Valley correspond to broad-scale climatic and tectonic conditions, suggesting that 'transition zone equivalents' and corresponding groundwater dynamics may occur in similar sedimentary settings throughout eastern Australia.